The Dialectics of the Archaic and the Post-Modern in Maghrebian Literature Written in French - Hédi Abdel-Jaouad (Studies in 20th & 21st Century Literature, 1991)
Maghrebian literature written in French has been since its inception a literature of and about the abyss. For the Maghrebian the abyss is esentially the space of modernity, that forbidden citadel of art, science and technology from which s/he was excluded and marginalized. Recently, writing of/in French has become the site/scene of a polemos between the archaic (identity) and the post-modern (difference). Our study of the archaic focuses on cultural, literary and critical knowledge and centers around two main themes: that of a beginning, that is a search for events in the past that explain the abyss (or retardation vis-à-vis the West), and that of an excavation, mainly of the collective unconscious, through the revamping of traditional and oral materials. On the other hand, the post-modern is not only that "moment" of delegitimization of modernity, as expounded by J.-F. Lyotard and other social theorists of post-modern knowledge; it is also a project, an esthetics and a theory to be, an epistemology of the future. In short, Maghrebian literature written in French, because it makes use of the Other's alphabet, is faced with a formidable challenge: can/will the alliance of the archaic and the post-modern bridge the abyss of modernity?
Keywords: Maghrebian literature; french; abyss; modernity; art; science; technology; marginalization; polemos; archaic; identity; post-modern; difference